2013
DOI: 10.1002/etc.2174
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation and toxicity of single‐walled carbon nanotubes to benthic organisms at the base of the marine food chain

Abstract: As the use of single-walled carbon nanotubes (SWNTs) increases over time, so does the potential for environmental release. This research aimed to determine the toxicity, bioavailability, and bioaccumulation of SWNTs in marine benthic organisms at the base of the food chain. The toxicity of SWNTs was tested in a whole sediment exposure with the amphipod Ampelisca abdita and the mysid Americamysis bahia. In addition, SWNTs were amended to sediment and/or food matrices to determine their bioavailability and bioac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
2
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 44 publications
(81 reference statements)
2
55
2
1
Order By: Relevance
“…For example, while evidence of the passage of CNTs through the gut of organisms such as earthworms and oligochaetes has been observed, evidence of their bioaccumulation has not been determined (Ferguson et al, 2008;Galloway et al, 2010;Petersen et al, 2008aPetersen et al, ,b, 2010. A similar finding was observed in a recent study assessing SWCNT bioaccumulation and trophic transfer using near infrared fluorescence (NIRF) which did not indicate bioaccumulation in the amphipod Ampelisca abdita and the mysid Americamysis bahia (Parks et al, 2013). However, these studies have generally not used advanced imaging techniques such as electron microscopy to investigate CNT absorption into the organism tissues, and thus absorption of small SWCNT masses could not be excluded when the SWCNT concentration in the whole organism was quantified.…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…For example, while evidence of the passage of CNTs through the gut of organisms such as earthworms and oligochaetes has been observed, evidence of their bioaccumulation has not been determined (Ferguson et al, 2008;Galloway et al, 2010;Petersen et al, 2008aPetersen et al, ,b, 2010. A similar finding was observed in a recent study assessing SWCNT bioaccumulation and trophic transfer using near infrared fluorescence (NIRF) which did not indicate bioaccumulation in the amphipod Ampelisca abdita and the mysid Americamysis bahia (Parks et al, 2013). However, these studies have generally not used advanced imaging techniques such as electron microscopy to investigate CNT absorption into the organism tissues, and thus absorption of small SWCNT masses could not be excluded when the SWCNT concentration in the whole organism was quantified.…”
Section: Introductionsupporting
confidence: 58%
“…However, additional research is needed to evaluate the sensitivity of this technique for SWCNTs embedded in various types of resins at low concentrations. Other emerging techniques such as NIRF microscopy are also promising alternatives for investigating the biodistribution of SWCNTs in organisms (Parks et al, 2013;Schierz et al, 2012). While a list of techniques that have been used to assess uptake and distribution of SWCNTs in ecological organisms has been recently provided , several additional novel techniques have also been published for SWCNT quantification in environmental matrices (Doudrick et al, 2012;Parks et al, 2013;Plata et al, 2012;Schierz et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative measurements (e.g., electron microscopy) do not determine the mass or concentration of CNTs but instead only determine their presence or absence, and thus the preferred methods for measuring biodistribution of CNTs are quantitative ones that determines the mass of CNT in organs. While there have been few quantitative CNT biodistribution measurements in organism tissues, numerous qualitative measurements have revealed no absorption of CNTs across the gut tract wall after uptake from the environment in either lower vertebrates or invertebrates 8, 48, 5255 . In addition, quantitative measurements of total CNT body burden in organisms have consistently revealed limited bioaccumulation or bioconcentration 8, 56 .…”
Section: General Findingsmentioning
confidence: 99%
“…Tests on functionalized SWCNTs injected into the bloodstream of mice showed no evidence of toxicity over 4 months of survival, and clinical and other laboratory parameters (Schipper et al 2008). Other studies indicated that SWCNTs are bioaccessible to marine benthic organisms but do not appear to accumulate or cause toxicity (Parks et al 2013). SWCNTs are possibly considered to be an effective alternative to antibiotics in dealing with drugresistant and multidrug-resistant bacterial strains.…”
Section: Introductionmentioning
confidence: 97%